Effects of exogenous oxytocin on serologic and seminal steroids and semen characteristics in rams - Bozkurt, T; Türk, G; Gür, S (My University, 2007)
The objective of this study was to investigate the effect of IV injection of oxytocin (OT) on serum and seminal plasma levels of oestradiol (E2), testosterone (T), dehydroepiandrosterone sulphate (DHEA-S), and semen characteristics in rams. Twelve 3-year-old Awassi adult rams were randomly divided into 2 equal groups (control and treatment). Physiological saline (0.5 ml) was injected IV into each ram in the control group, whereas OT was administered IV at a single dose of 5 IU to each ram in the treatment group. Blood samples were collected from the jugular vein and semen samples were taken by an electroejaculator from all rams sequentially at 10, 60, and 120 min after the IV injection of physiological saline or OT. Administration of OT had no effect on blood or seminal plasma E2 or DHEA-S levels, or on serum T at any collection time compared to the control group. However, while OT increased significantly the level of seminal plasma T at 10 min, its effect was absent at 60 and 120 min after the injection compared to the control group. OT did not alter the semen viscosity, sperm motility, or abnormal sperm rate at all times in comparison to the control values. Although semen volume, mass activity, sperm concentration, total sperm number, and total motile sperm number of the treatment group increased significantly at 10 min compared to the control group, all these parameters decreased markedly at 60 and 120 min in comparison with 10 min after injection in both the control and treatment groups. In conclusion, exogenous OT increases seminal plasma T, semen volume, mass activity, sperm concentration, total sperm number, and total motile sperm number in the first ejaculate of the rams 10 min after the IV administration.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Oxytocin oestradiol testosterone dehydroepiandrosterone sulphate semen characteristics ram